Low-dose aspirin does not affect the renal function of microalbuminuric type 2 Diabetic patients - Camargo, Eduardo Guimaraes; Weinert, Leticia Schwerz; Soares, Ariana Aguiar; Ferreira, Mariana Nunes; Araujo, Gustavo Neves; Silveiro, Sandra Pinho (Clinical and Biomedical Research, 2012)
BACKGROUND: Low-grade inflammation has been implicated in the pathogenesis of diabetic nephropathy, and anti-inflammatory drugs could be potentially useful as a therapeutic tool. The aim of this study was to analyze the effect of low-dose aspirin (300 mg/d) on urinary albumin excretion (UAE) and glomerular filtration rate (GFR) levels of microalbuminuric type 2 DM patients. METHODS: In this randomized, double-blind, crossover, placebo-controlled study, 18 microalbuminuric (UAE=30-300 mg/24 h) type 2 DM patients received aspirin (300 mg/d) or identical placebo for 8 weeks, with a 6-week washout period. The patients were aged 56±9 years, had a diabetes duration of 16±7.5 years; 11 (61%) were female, and they were all using enalapril 10 mg bid. GFR was measured by 51Cr-EDTA single-injection method and UAE by immunoturbidimetry. The sample-size calculation showed that 17 patients were needed to detect a 30% change in UAE (α= 0.05 and β= 0.20). RESULTS: After 8 weeks of treatment, there were no significant differences between placebo and aspirin, respectively, regarding UAE [57.7 (8.9-420.0) vs. 63 (8.2-272.0) mg/24 h; P=0.45] and GFR (108±34 vs. 111±47 ml/min/1.73 m2; P=0.90). C-reactive protein levels [2.72 (0.34-10.3) vs. 2.03 (0.25-10.3) μg/l; P=0.21] were comparable after placebo and aspirin, respectively. There were no period (P=0.41) or carry-over effects (P=0.49). CONCLUSION: Low-dose aspirin did not affect GFR and UAE levels of microalbuminuric type 2 DM. It seems that the putative low-grade inflammation of diabetic nephropathy does not respond to these low doses of the drug.